Complementary and alternative medicine (CAM) practices and dietary patterns in children with inflammatory bowel disease in Singapore and Malaysia - Ong, F. (Elsevier (Singapore) Pte Ltd, 2022)
10.1016/j.pedneo.2017.12.007